Ensino artístico no desenvolvimento de Cabo Verde no combate à exclusão social - Moreira, Félix Duarte (2019)
The objective of this dissertation, Teaching Artistic in the Development of Cape Verde in Combating Social Exclusion, is to contribute to improve artistic education, articulating to the theory and practice, using the artistic potential of Cape Verdeans, in the valorization of human resources, using the schools in the service of society, we analyzed the five chapters and sub-chapters above all, the educational system, so that we can perceive and perpectivate the future, promoting quality and excellence, phase to the challenges of teaching for the 21st Century. We used the experiences "work as a Monitor of Handicrafts, in the old Preparatory Cycle School of Complementary Basic Education of the Municipality of Santa Cruz and School Complex Regina Silva, City of Praia-Cape Verde" and "technician in (FBAUL) -Faculty of Fine Arts of the University of Lisbon ", linked to the practice of artistic teaching for a greater reflection (such as improving art teaching), creating an artistic and museological culture in the fight against school failure and social exclusion." Learning more to act better "Amílcar Cabral. The method we used was based on my training, professional activities and above all on the reading of several books, since since our youth we have always been linked to teaching in some countries (Cape Verde, Portugal and Angola), working and exercising a function of the teacher. summary, we finalize, we propose, the Art Education Project of Cape Verde-21, which would take place at the Morabeza Meeting 365 days (with a cultural agenda from January to December), from Ilha de Santo Antão to Ilha Brava